"Enthusiastic Admiration Is the First Principle of Knowledge and Its Last": A Qualitative Study of Admiration for the Famous. (April 2021) - Meng-Lewis, Yue; Xian, Huiping; Lewis, Gavin; Zhao, Yupei
The concept of fame has been associated with celebrities, wealth, attractiveness, and social recognition. Nevertheless, people have admiration for the famous who may not be celebrities. Admiration is regarded as one of the emotions of appreciation, or moral emotions, triggered by positive appraisals of excellence. It is present when seeing extraordinary displays of skills talent or achievement. However, theoretical and empirical research on admiration and its psychological effects on people are scarce. In this article, we discuss a qualitative study that explores a collection of experiences of admiration for the famous. Based on 26 in-depth interviews with residents in southern England, we explored why people admire famous individuals and how the experience may produce positive attitudes and behaviors. We found that through admiring famous individuals who are perceived to share similar interests and attributes, people may develop positive thinking about their own lives and may be more active in seeking new opportunities or engaging in self-growth. We also discuss the potential problems of admiration. This exploratory research contributes to the literature of positive psychology and has implications for furthering the understanding of people's well-being.